2017
DOI: 10.1007/s10616-017-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mincing method for isolation of adipose-derived stem cells from pregnant women fat

Abstract: The success of stem cell application in regenerative medicine, usually require a stable source of stem or progenitor cells. Fat tissue represents a good source of stem cells because it is rich in stem cells and there are fewer ethical issues related to the use of such stem cells, unlike embryonic stem cells. Therefore, there has been increased interest in adipose-derived stem cells (ADSCs) for tissue engineering applications. Here, we aim to provide an easy processing method for isolating adult stem cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Mechanical disruption finely dissociates the tissue and, by increasing the surface area of the tissue, provides a more efficient enzymatic digestion, resulting in an increased MSC yield (Table ). The method is supported by a study investigating excised adipose tissue (Li et al., ), where the authors found an increase in SVF cell yield with prior tissue disruption for 15 sec before enzymatic digestion. Their study, however, reports specific yield of the heterogeneous SVF population and not a precise measurement of phenotypically characterized MSCs.…”
Section: Commentarymentioning
confidence: 96%
See 1 more Smart Citation
“…Mechanical disruption finely dissociates the tissue and, by increasing the surface area of the tissue, provides a more efficient enzymatic digestion, resulting in an increased MSC yield (Table ). The method is supported by a study investigating excised adipose tissue (Li et al., ), where the authors found an increase in SVF cell yield with prior tissue disruption for 15 sec before enzymatic digestion. Their study, however, reports specific yield of the heterogeneous SVF population and not a precise measurement of phenotypically characterized MSCs.…”
Section: Commentarymentioning
confidence: 96%
“…To optimize MSC extraction, different isolation techniques have been investigated (Domenis et al., ; Faustini et al., ), including enzymatic isolation, mechanical isolation, and automated systems. Only a single published study combines enzymatic and mechanical MSC isolation (Li et al., ), and these authors describe an increased yield of the stromal vascular fraction (SVF) from excised adipose tissue. However, excision of adipose tissue is a more complicated procedure than aspiration.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent adipose tissues were washed with Dulbecco's phosphate buff ered saline (D-PBS) separately performed in sterile petri dish. Adipose tissue samples was removed from D-PBS, placed into the 100 mm 2 petri dish and cut into the more small pieces (1-2 mm 2 ) for mincing process [26] . After this mincing process, 1.5 g of fat tissue + 1.5 mL of 0.08% isotonic content were added to 2 centrifuge tubes (15 mL volume).…”
Section: Collection Of Adipose Tissue and Svf Preparation Protocolmentioning
confidence: 99%